Screening for Antibacterial Active Fractions from Kummerowia striata - Li, Lihong; Li, Yali; Li, Kun; Liu, Haohua; Jin, Xin; Cui, Zeshi; Zhang, Dongfang (Asian Journal of Chemistry, 2014)
To screen the antibacterial effective fractions from the extract of Kummerowia striata and further mechanism of antibacterial activity. The effective fractions were screened with AB-8 macroporous resins and analyzed by high performance liquid chromatography, Minimal inhibitory concentrations (MICs) of the extract against Staphylococcus aureus were determined using serial dilution method. The ultrastructural morphology of cells of S. aureus was observed under electron microscopy. Three compounds including genistein, kaempferol, galuteolin from the powder were identifed. MIC of 70 % ethanol eluate, the most effective fraction, was 2.3 mg mL-1. Through the observation of the ultrastructural morphology of cells of S. aureus under electron microscopy, the cell walls were broken and the edge of cell wall of S. aureus was irregular. The results show that the total flavones might be the main chemical components with antibacterial activity and the mechanism against S. aureus is breaking cell wall and disintegrating cytoplasm of bacteria.